A new first-principles model to predict mild and deep surge for a centrifugal compressor. (1st April 2022) - Powers, Katherine; Kennedy, Ian; Archer, Jamie; Eynon, Paul; Horsley, John; Brace, Chris; Copeland, Colin; Milewski, Paul
Abstract: Centrifugal compressors are used in many applications, including automotive turbochargers. Surge is an instability that occurs at low mass flow rates that is often damaging. Even mild surge produces noise characteristics that cause problems with customer acceptance. It is therefore important to be able to predict both mild and deep surge onset. In existing literature, models resulting in cubic-shaped compressor characteristics have been developed from first principles. This paper extends these to include diffuser recirculation and show a new quintic-like shape for compressor characteristics which, for the first time, can differentiate between mild and deep surge. These characteristics are incorporated into a model for an experimental facility and resulting simulations show remarkable fit to experimental data. The model allows for variations in both space and time, so simulations can capture wave dynamics in the pipework. The model captures: stable operation, mild surge, transition from mild to deep surge, deep surge, and the potential for a stable quiet period beyond the surge limit. Furthermore, the model can provide physical explanations for the surge dynamics observed. This combined with the model's predictive ability will be of help to turbocharger manufacturers during early design stages, prior to experimental tests or detailed CFD studies. Graphical abstract: Image 1 Highlights: New reduced-order predictive model for surge in centrifugal compressors. New proposed quintic-like shape for compressor characteristics. Both mild and deep surge captured in a surge model for the first time. First time the observed mid-surge quiet period has been captured and explained. Proposed new understanding of physics behind observed surge phenomena.